THREE-DIMENSIONAL NUMERICAL INVESTIGATION ON LAMINAR FORCED CONVECTION AND HEAT TRANSFER IN A CIRCULAR TUBE INSERTED WITH RIGHT TRIANGULAR WAVY SURFACES - Withada Jedsadaratanachai; Amnart Boonloi (My University, 2017)
A premiere free-access and peer-reviewed frontier journal site, serving the needs of the thermal-fluids community. See the latest research or submit an article. Quickly share your research with the global thermal-fluids community, for increased citations and impact at no cost.
Keywords: Thermal fluids; Forced convection; Frontier; Lattice Boltzmann Simulation Studies